Effects of 8-week in-season upper and lower limb heavy resistance training on the peak power, throwing velocity, and sprint performance of elite male handball players - Hermassi, S.; Chelly, M. S.; Tabka, Z.; Shephard, R. J.; Chamari, K. (The Journal of Strength and Conditioning Research, 2011)
The aims of this study were to test the potential of in-season heavy upper and lower limb strength training to enhance peak power output (Wpeak), vertical jump, and handball related field performance in elite male handball players who were apparently already well trained, and to assess any adverse effects on sprint velocity. Twenty-four competitors were divided randomly between a heavy resistance (HR) group (age 20 ± 0.7 years) and a control group (C; age 20 ± 0.1 years). Resistance training sessions were performed twice a week for 8 weeks. Performance was assessed before and after conditioning. Peak power (Wpeak) was determined by cycle ergometer; vertical squat jump (SJ) and countermovement jump (CMJ); video analyses assessed velocities during the first step (V1S), the first 5 m (V5m), and between 25 and 30 m (Vpeak) of a 30-m sprint. Upper limb bench press and pull-over exercises and lower limb back half squats were performed to 1-repetition maximum (1RM). Upper limb, leg, and thigh muscle volumes and mean thigh cross-sectional area (CSA) were assessed by anthropometry. Wpeak (W) for both limbs (p < 0.001), vertical jump height (p < 0.01 for both SJ and CMJ), 1RM (p < 0.001 for both upper and lower limbs) and sprint velocities (p < 0.01 for V1S and V5m; p < 0.001 for Vpeak) improved in the HR group. Upper body, leg, and thigh muscle volumes and thigh CSA also increased significantly after strength training. We conclude that in-season biweekly heavy back half-squat, pull-over, and bench-press exercises can be commended to elite male handball players as improving many measures of handball-related performance without adverse effects upon speed of movement.